Effect of microwave-assisted system on transesterification of castor oil with ethanol - Hincapié, Gina M.; Institute of Chemistry, Universidad de Antioquia, Medellín, Colombia. (2014)
A systematic study of microwave-assisted transesterification of castor oil was conducted in the presence of ethanol and of potassium hydroxide as catalyst. Effects of various reaction parameters such as reaction time, catalyst concentration, reaction temperature and ethanol-oil molar ratio were analyzed. Ethyl esters were successfully produced by microwave-assisted transesterification. The maximum yield was 80.1% at 60°C, 10:1 alcohol: oil molar ratio, 1.5% potassium hydroxide and 10 min. The results show that there was a reduction in reaction time for microwave-assisted transesterification as compared to conventional heating, yields were slightly affected by temperature from 40-70ºC; this indicates a significant effect of microwaves even at low temperatures.